Fostering personalized learning in flipped classroom: A systematic literature - Wiwik Rahayu; Arinda Frismelly; Fenti Amelia Sari (Universitas Negeri Padang, 2026)
This systematic review examines the integration of personalized learning into the flipped classroom model in higher and vocational education over the past five years. The aim of this study is to examine personalization strategies in the flipped classroom, identify the supporting technologies used, and identify research gaps from previous studies. The research method employed was a literature review using the PRISMA 2020 guidelines, conducted via Scopus and Google Scholar covering the years 2019–2024, with Boolean search terms including ‘personalized/individualized learning’, ‘flipped classroom’, and ‘vocational education/training’. This method yielded eleven articles, which were used to examine personalized learning in the flipped classroom. This study demonstrates improvements in achievement, motivation, engagement, and self-regulation through the use of personalized learning in the flipped classroom. Challenges encountered include platform instability, increased workload for instructors, demands for data literacy, and students’ concerns regarding monitoring. It is hoped that these findings will contribute to academics, educational institutions, and policymakers in designing personalized learning within the flipped classroom.